AVALIAÇÃO DE EQUAÇÕES DE PERDA DE SOLO PARA USO EM MODELAGEM DISTRIBUÍDA DE GRANDES BACIAS - Almeida, Gabriella Passamani Moreira de (2021)
Erosion is one of the main factors of soil degradation and can cause several changes in its structure, such as increased production and transportation of sediments and silting of water bodies. For this reason, hydrosedimentological studies are becoming increasingly importante. Mathematical models have been widely used to understand the dynamics of sediments in watersheds. In large-scale basins, conceptual and distributed models, which integrate a hydrological module in their structure are usually preferred. The MGB-SED is a hydrosedimentological model coupled to the MGB model, which uses the MUSLE equation, to calculate sediment production on a daily time scale. Besides MUSLE, in large scale distributed modeling for continuous simulation, other soil loss equations have potential for these applications. The objective of this study was to evaluate the potential of the soil loss equations, MUSLE, USLE-M and RUSLE2 for use in distributed modeling in the Doce River watershed, using the MGB-SED model. The seasonal variability of suspended sediments and water quality parameters, turbidity and total suspended solids were evaluated, in comparison with observed sediment concentration data, the spatial variability of the annual sediment load generated in each mini-basin and of suspended sediments in each stretch of river in addition to the relationship between solid flow and net flow for each equation. The evaluation carried out showed that the results obtained by the three equations were able to represent the temporal variability of suspended sediments along the Doce River watershed and its sediment dynamics, however, the results obtained with MUSLE showed the adjustments closest to the observed data and the best statistics for most evaluated stations, followed by the USLE-M equation and finally RUSLE2.